MANAJEMEN PENGELOLAAN HUTAN PRIBADI DI DESA SINTUWU KECAMATAN PALOLO KABUPATEN SIGI - Abd Rasid; Adam Malik; Andi Sahri Alam (Universitas Tadulako, 2018)
Private forest is a concept of forest management that places society as the main sector in maintaining and using forest function, while the government has role as facilitator that supports the farmers community. The management and the development of private forest in Sintuwu village Palolo subdistrict is a collaboration of Forestry and Plantation Department of Sigi District. The research was conducted for three months, began on April up to the month of June 2015, located in Sintuwu village Palolo subdistrict Sigi district. The research aimed to find out of how the process of Private Forest Management was done by the society. Data gathering was done by observing and interviewing with questionnaire. The data gathered analized descriptively. The result of the research showed that the management program of the private forest that made by Forestry and Plantation by full involvement of farmers community of Sintuwu village that established, and based on the result of interviewing the respondents of the farmers community who said that less attention from Forestry and Plantation Department then the Private Forest management was done individually without any coordination. All farmers community did the private forest management that included infrastructure, planting area management, planting, maintaining and supervising by their own ways without monitoring by the government, therefore at the end of the planting the plant, it was ignored for them less of information and no coordination of the Forestry and Plantation Department about the next step that should be done in relation to the Private Forest management itself.Keywords: Institution, Society and Government, Private Forest